Salinity Structure Within The Estuary Of Bintuni Bay, At The Southern Part Of Bird Head Of West Papua, Indonesia - I Wayan Nurjaya (Pusat Riset Kelautan, 2016)
Bintuni Bay is a semi-closed bay which a lot of big rivers flow into the bay and bring a huge amount of freshwater. This bay is not directly connected to the open sea but separated by the Berau Bay. The bay of Berau has wider bay mouth as well as deeper than Bintuni Bay, the deepest part more than 70 m located at the center part of bay. Tidal force generated offshore is able to push higher salinity water (HSW) mass further into the inner bay, otherwise the low salinity water (LSW) mass pushed out toward the head of the bay. In the area where LSW and HSW masses meet each other is found steep salinity gradient (salinity front). Two times field observations were conducted with lowered CTD (Conductivity Temperature Depth) sensor from the surface layer until one meter above seabed at 30 stations, either at the end of north-east monsoon (March 2013) or at south-east monsoon (July-August 2013). The HSW mass was dominant found at deeper layer and southern side of the bay, while the LSW mass occupied surface layer at the northern side of the bay.